Psychological aspects of motivation - Adam Pawlak (Kazimierz Wielki University, 2019)
The purpose of the article is to make people aware of what motivation and motivating employees are in organizations. The article discusses definitions and sources of motivation, historical and contemporary views on motivation, tools for comprehensive reward, remuneration as an instrument of motivational impact, success determinants and assessment of the motivation system, motivational impact of employee assessment and motivation in the face of organizational changes.